An examination of the definition and development of expert coaching - Wiman, M.; Salmoni, A. W.; Hall, C. R. (International Journal of Coaching Science, 2010)
The aim of this paper is twofold: first, to examine how coaching expertise is defined and second, to investigate how this expertise develops over time. This research involved semi-structured interviews with elite athletes and elite coaches and was done in the tradition of grounded theory. Results suggested that there is a need to go beyond identifying a coach as an expert based on the performance of his/her athletes. Some of the additional criteria suggested included: be recognized by peers (other coaches) as experts; be recognized by athletes as experts and have successful athletes/teams at any level of competition. In keeping with the tradition of studying expertise, we suggest that research in coaching expertise would benefit by being more specific.